Single crystals growth of hexaferrits M-type MTixCoxFe₁₂–₂xO₁₉ (M = Ba, Sr) by floating zone and investigation of their magnetic and magnetoelectric properties - Balbashov, A.M.; Voronchikhina, M.E.; Iskhakova, L.D.; Ivanov, V.Y.; Mukhin, A.A. (Физика низких температур, 2017)
Floating zone melting method with optical heating is elaborated to grow single crystals of the substituted hexaferrites BaTixCoxFe₁₂–₂xO₁₉ and SrxTixCoxFe₁₂–₂xO₁₉ (0.8 ≤ x ≤ 2). The dynamics of the growth process is studied and results of the analysis of impurity phases appearing in the initial stages of the crystal growth are presented. Compositions and unit-cell parameters of crystals are determined. Electrical, magnetic and magnetoelectric properties of grown crystals are investigated at temperatures 2–365 K and magnetic fields up to 50 kOe. It is shown that the resistivity of annealed in oxygen crystals at room temperature is ∼10⁶ Ohm·cm while at helium temperatures the crystals become good insulators. Magnetic measurements reveal conical spin structures in the crystals at some concentrations and temperatures. Magnetic field induced electric polarization of the low value (∼0.3 μC/m²) is detected at liquid helium temperatures for compositions with Ti and Co concentrations x = 0.8–0.9.